Aesthetics as a Philosophical and Theological Space in the St. Francis of St. Bonaventure’s Major Legend - Lázaro Pulido, Manuel (Religions, 2022)
This paper demonstrates that the figure of St. Francis of Assisi, as expounded by St. Bonaventure in his work Legenda Major (Major Legend), cannot be understood without certain philosophical and theological keys. Following an expository methodology, we point to Saint Francis as a theological aesthetic model. In this sense, we focus on five characterisations found in the Major Legend, introducing their aesthetic meaning, as well as the philosophical and theological significance of St. Bonaventure. We refer to St. Francis as a contemplator of nature, lover of poverty, an imitator of the crucified Christ, a brother of humankind and a Lord’s knight and minstrel, to conclude that the aesthetic model of St. Francis, as found in St. Bonaventure, can only be understood starting from theological (mystical) and philosophical ascension.